Rasionalitas Gerakan Kewirausahaan Organisasi Tarekat SiddÃ®qÃ®yah di Jombang - Munir, Misbahul (Program Pascasarjana UIN Sunan Ampel Surabaya, 2015)
This article aims to reveal the values of local wisdom explored from the teachings of the SiddÃ®qÃ®yah order which drives the emergence of high spirit of entrepreneur-ship. The article demonstrates that the spirit of entrepreneur-ship within the SiddÃ®qÃ®yah order is strongly related to its teachings, doctrines and culture, such as that of the unity between faith and humanity, the eight points of readiness for the SiddÃ®qÃ®yah membership, and the doctrine of âsantriâ (disciple). In attempts to earn living, they run business enterprise through promoting the principle of hard-work and good business management, in addition to implementing spiritual and social capital in achieving success in business. They believe in and feel the strength of prayer (duâÃ¢â), certain rituals, and the importance of belief and harmony to achieve success in business. The teachings, doctrines and culture of the SiddÃ®qÃ®yah order influence the understanding towards the meaning of wealth or property, and occupy an important position in the life of the SiddÃ®qÃ®yah followers. For them, property or wealth has double meaning; it is not only meant in economic context, but also understood in other meanings, i.e., social, spiritual, cultural, and philosophical.